Gastric trichobezoar and Rapunzel syndrome: a case report - Gupta, Abhishek; Gupta, Panna Lal (International Surgery Journal, 2020)
Giant gastric trichobezoars are unusual form of foreign body found in stomach of mostly young adolescent females which may lead to morbidity and high mortality 30%, if goes unnoticed. These females have history of trichophagia or trichotillomania. This report is of a 12- year old young adolescent female presented with epigastric pain and mass. An exploratory laparotomy with anterior gastrotomy was performed and a giant trichobezoar with a very large tail of 2.5 ft was removed, weighing 2.52 kg. She recovered well and was discharged on 7th post-operative day. Patient was advised for psychiatric follow up.